Development of SLE among "potential SLE" patients seen in consultation: long‐term follow‐up. Issue 12 (23rd May 2014) - Al Daabil, M.; Massarotti, E. M.; Fine, A.; Tsao, H.; Ho, P.; Schur, P. H.; Bermas, B. L.; Costenbader, K. H.
Summary: Objective: To identify factors associated with development of systemic lupus erythematosus (SLE) among patients evaluated at a tertiary care Lupus Center for potential SLE. Methods: We identified patients first seen at the Brigham and Women's Hospital Lupus Center between 1 January 1992 and 31 December 2012 and thought to have potential SLE by a board‐certified rheumatologist. All had 1–3 SLE ACR criteria at initial visit and > 2 follow‐up visits ≥ 3 months apart. We reviewed medical records through 15 May 2013 for: SLE signs and symptoms, autoimmune serologies, prescriptions and diagnoses by board‐certified rheumatologists. Bivariable analyses and multivariable logistic regression models were used to identify independent predictors of developing SLE. Results: Two hundred and sixty four patients met inclusion criteria. At initial visit, mean age was 39.2 (SD 12.4) years, 94% were female and 67% white. Mean number of SLE ACR criteria was 2.7 (SD 1.0) and 88% were antinuclear antibody (ANA) positive at initial consultation. Mean follow‐up time was 6.3 (SD 4.3) years and 67% were prescribed hydroxychloroquine in follow‐up. At most recent visit, 56 (21%) had been diagnosed with SLE; 47 (18%) were thought not to have SLE and 161 (61%) were still considered to have potential SLE. In multivariable regression models, oral ulcers (OR 2.40, 95% CI 1.03–5.58), anti‐dsDNA (OR 2.59, 95% CI 1.25–5.35) and baseline proteinuria or cellular casts (OR 16.20, 95% CI 1.63–161.02) were independent predictors of developing SLE. The most common other final diagnoses included fibromyalgia, Sjögren's syndrome, mixed connective tissue disease and cutaneous lupus. Conclusion: Among patients with potential SLE at initial consultation, 21% were diagnosed with definite SLE within 6.3 years. Oral ulcers, anti‐dsDNA and proteinuria or cellular casts were independent predictors of developing definite SLE. A better means of accurately identifying those who will develop SLE among those presenting with potential disease is necessary.